PROBLEMS OF FORMATION OF RUSSIAN INNOVATIVE AGRICULTURAL TRACTORS FLEET - V. M. Kryazhkov; Z. A. Godzhaev; V. G. Shevtsov; S. G. Gurylev; A. V. Lavrov; A. N. Osherov (Сельскохозяйственные машины и технологии)
In the market of agricultural tractors of Russia in 2013 were 900 domestic models, or 3.4 percent. There were produced 7655 tractors, 6707 from which were foreign models. It was revealed that purchasing power of the agricultural organizations appears at profitability not less than 20 percent. Because this indicator is 5.2-11.7 percent lower, agricultural enterprises are not able to turn over their fleets. The authors have presented the forecast of development of tractor fleet till 2020 taking into account the solution of national tasks, including import substitution and dynamics of the annual purchases providing its realization. Methodology of development of the State program of food import substitution based on tractor fleet revival as conditions of self-sustainability of Russia was proposed. A role of tractor fleet as multiplier in development of the mechanized agricultural production was revealed. The first-priority problem is working out of tractors of economic category.